Developing Logistics and Supply Chain for Export Successl SMEs in Thailand - Sutuntivorakoon, Nuthapong (2006)
This Study aims to investigate some important issues in Supply Chain Management (SCM)in order to be success in Thai exporting business. A Thai SME in paper industry is chosen to be a case study to see how its current supply chain activities are implemented and to explore possible solutions to problems arisen in the supply chain. The literature review of SCM is used as a guideline to develop questions for an interview of the case company. The qualitative interview aims to understand key potential problems of their supply chain activities and to achieve the detailed information. Additionally, the condition of Thai export industry is also reviewed to give an understanding of export procedures in Thailand and some organisations that support export businesses. Through the analysis of the case study, current situation of SCM is explored, key problems are identified (e.g. forecasting inaccuracy, warehouse problem, problem of organizational structure, and customer debts) and possible solutions are suggested (e.g. inventory management, warehouse management, organizational restructuring, customer relationship management, human resource training, and performance assessment). However, the SCM is currently considered unimportant for the case company, but there is a long-term possibility and potential of using it as the business grows. It cannot be ignored to say that SCM has seen as a crucial tool to be success in todays businesses, not only in export businesses but in every aspect of businesses. In order for Thai SMEs to be able to compete in the competitive global markets, their supply chain strategies are needed to be well-studied and thoroughly reviewed. Good supply chain strategies adopted would lead to huge savings in total costs and increase in service level.